ASSESSMENT OF ACHIEVEMENT OF BUSINESS STAFF COOPERATIVE REPUBLIC OF INDONESIA "MEGA PROSPER" SMEA 3 YOGYAKARTA - One, Sujiyanto; Lastari, SE.,MM, Siwi; Murdo,M.Si, Drs. Yuri (Management, 2010)
The study titled Assessment of Job Performance Employees Cooperative Enterprises of the Republic of Indonesia "Mega Prosperous" SMEA 3 Yogyakarta was conducted in February to March 2010. This study aims to determine the Assessment of Job Performance Employees Cooperative Republic of Indonesia "Mega Prosperous" SMEA 3 Yogyakarta in 2004 until the year 2008. This research used diskristif that is research done solely object or event described the situation in detail and depth. Data collection method used was a review of the data the Financial Report and Annual Member Meeting. Cooperative Achievement Assessment is based on the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 06/Per/M.KUKM/V/2006. Based on data analysis of the Financial Report and Annual Meeting of Members, that the Employee Cooperative Republic of Indonesia "Mega Prosperous" SMEA 3 Yogyakarta has a good value with an average score of 66.5 but in business volume, net assets, own capital, which is still very SHU low that has not reached the average value which is required as a co-operative achievement of 78.00 so that the Employee Cooperative Republic of Indonesia "Mega Prosperous" SMEA 3 Yogyakarta yet to be classified as cooperative achievement in 2004 until 2008. Keywords: work performance, employees, cooperatives